Odpowiedzi

Najlepsza Odpowiedź!
2010-02-03T22:45:14+01:00
A) 1/3x-x=2+2
-2/3x=4 /*(-3/2)
x=4*(-3/2)
x=-12/2
x=-6

b) 1-6/7x=4/7
-6/7x=4/7-1
-6/7x=-3/7 /*(-7/6)
x= 21/42
x=1/2

c) 6 (¼x - 2)=18
6/4x-12=18
3/2x=18+12
3/2x =30 /*2/3
x=60/3
x=20

d) x/6 - ⅙ = 1
1/6x=1+1/6
1/6x=1 i 1/6
1/6x=7/6 /*6
x=7

e)-2 (2x-1) = x/3
-4x+2=1/3x
-4x-1/3x=-2
-4 i 1/3 x =-2
-13/3 x = -2 /*(-3/13)
x=6/13

f) 2/5 (3 - x) = -2
6/5-2/5x=-2
-2/5x = -2 -1 i 1/5
-2/5x=-3 i 1/5
-2/5x = -16/5 /*(-5/2)
x =8

g) 3/4 (2-3x) = -6
6/4 - 9/4x=-6
3/2-9/4x=-6
-2 i 1/4x=-6-1 i 1/2
-9/4 x=-7 i 1/2
-9/4 x=-15/2 /*(-4/9)
x = 10/3
x=3 i 1/3

h) 1/5 (x-3) = 9 - x
1/5x -3/5 = 9-x
1/5 x +x = 9+3/5
1 i 1/5x = 9 i 3/5
6/5 x = 48/5 /*5/6
x =8

i) 0,6 + x / 2 = x + 1
1/2 x -x = 1-0,6
-1/2 x = 0,4 *(-2)
x = -0,8
96 4 96
przykład i) jest źle
całe zadanie jest źle
Dzieki
hehe